Investigating the Influence of Indecision on Customer’s Decision Satisfaction - Huang, Hui-Hsin (Research Center and Case Clearing House PPM School of Management, 2024)
Indecision behavior usually appears in daily life, especially on purchase occasions. This trait in the decision process will influence customers' decision satisfaction. This research proposes a Bayesian model to portray the phenomena of indecision and decision satisfaction. The decision satisfaction is a random variable with the prior density in which the parameter given in the density function is demonstrated as indecision. The empirical data of Google Analytics is used to measure indecision behavior and model calibration. Finally, the conclusion is shown to make an application in actual consumer behavior research. This research can help managers control the tendency of indecision to achieve higher decision satisfaction. In advance, the impact factors of indecision can be investigated to design more incentive and attractive platforms to accelerate the payment process